2002
DOI: 10.1175/1520-0477(2002)083<0279:coaecb>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Comments on “Atmospheric Disturbance Caused by Human Modification of the Landscape”

Abstract: This new and important professional and personal networking tool allows you to make contact with thousands of colleagues. The directory, which is searchable by last name, lists mailing addresses, telephone numbers, and electronic addresses of our members. It's easier than ever before to keep in touch. The membership directory is password protected so that only our individual members may gain access. Visit the directory site to create your personalized user profile. Start taking advantage of this invaluable mem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 9 publications
(10 reference statements)
0
3
0
Order By: Relevance
“…This hypothesis is in agreement with the IPCC-reported observation of increased precipitation in all tropical forest regions in the last three decades (Folland et al 2001), although this may equally be due to natural variability or global warming. Furthermore, we recognize that there is still significant debate about the extent to which mesoscale circulation changes might affect larger-scale patterns (Doran and Zhong 2002;cf. Weaver and Avissar 2002).…”
Section: R Ecent Intensification Of Thementioning
confidence: 97%
“…This hypothesis is in agreement with the IPCC-reported observation of increased precipitation in all tropical forest regions in the last three decades (Folland et al 2001), although this may equally be due to natural variability or global warming. Furthermore, we recognize that there is still significant debate about the extent to which mesoscale circulation changes might affect larger-scale patterns (Doran and Zhong 2002;cf. Weaver and Avissar 2002).…”
Section: R Ecent Intensification Of Thementioning
confidence: 97%
“…This is particularly interesting given the ongoing discussion regarding whether mesoscale circulations in the SGP are a function of vegetation cover (WEAVER and AVISSAR, 2001) or topography (DORAN and ZHONG, 2001). Using 20 m elevation slices spanning the WRW, the percent coverage of each LULC classification was determined.…”
Section: Relationships Between Surface Characteristics and Land Use/lmentioning
confidence: 99%
“…However, there have been debates regarding the importance and spatial scales of secondary circulations induced by land surface heterogeneities, particularly those of vertical velocity and turbulent fluxes (Doran & Zhong, 2002; Kang & Davis, 2008, 2009; Weaver, 2009; Weaver & Avissar, 2001). Zhong and Doran (1998) studied mesoscale model simulations over the Southern Great Plains (SGP) using observation‐based surface fluxes and large‐scale winds for boundary conditions and concluded that mesoscale secondary circulations and their influence on the mean properties over a large domain (e.g., a few hundreds of km) are substantially smaller than those found with idealized heterogeneities and zero background winds.…”
Section: Introductionmentioning
confidence: 99%